Gene–gene interactions between TGF-β/Smad3 signalling pathway polymorphisms affect susceptibility to knee osteoarthritis. Issue 6 (11th June 2015) - Su, Sui-Lung; Yang, Hsin-Yi; Lee, Herng-Sheng; Huang, Guo-Shu; Lee, Chian-Her; Liu, Wan-Shan; Wang, Chih-Chien; Peng, Yi-Jen; Lai, Ching-Huang; Chen, Ching-Yang; Lin, Chin; Pan, Yu-Ting; et al.
Abstract : Objective: Transforming growth factor/Smad family member 3 (TGF)-β/Smad3 signalling is essential for maintaining articular cartilage. A relationship between the genetic variants of TGF-β itself, TGF-β signalling and binding molecules, and osteoarthritis (OA) has been reported. Although variants of candidate genes have become prime targets for genetic analysis, their detailed interplay has not been documented. Our goal was to establish whether single nucleotide polymorphisms (SNPs) of TGF-β1, TGF-βRI, Smad3 and tissue inhibitor of metalloproteinases 3 (TIMP3), and their interactions, are associated with knee OA. Design: We performed a case–control association study and genotyped 518 knee patients with OA and 468 healthy controls. All participants were genotyped for TGF-β1 (rs1800469C/T), TGF-βRI (rs1590A/G), Smad3 (rs12901499A/G and rs6494629T/C), and TIMP3 (rs715572G/A and rs1962223G/C) polymorphisms by polymerase chain reaction–restriction fragment length polymorphism analysis. Multifactor dimensionality reduction (MDR) was used to identify gene–gene interactions. Results: Significant associations were observed for TIMP3 rs715572G/A polymorphisms in knee patients with OA and healthy individuals. The GA heterozygote in TIMP3 (rs715572G/A) was significantly associated with OA (p=0.007). Patient stratification using the Kellgren–Lawrence grading scale showed significant differences in TIMP3 rs715572G/A genotypes between grade 4 knee OA and controls. By MDR analysis, a two-locus model (Smad3 rs6494629T/C and TIMP3 rs715572G/A) of gene–gene interaction was the best for predicting knee OA risk, and its maximum testing accuracy was 57.55% and maximum cross-validation consistency was 10/10. Conclusions: TIMP3 rs715572G/A is a candidate protective gene for severe knee OA. Gene–gene interactions between Smad3 rs6494629T/C and TIMP3 rs715572G/A polymorphisms may play more important protective roles in knee OA.